2016
DOI: 10.1186/s40064-016-3655-6
|View full text |Cite
|
Sign up to set email alerts
|

A new bioinformatic insight into the associated proteins in psychiatric disorders

Abstract: BackgroundPsychiatric diseases severely affect the quality of patients’ lives and bring huge economic pressure to their families. Also, the great phenotypic variability among these patients makes it difficult to investigate the pathogenesis. Nowadays, bioinformatics is hopeful to be used as an effective tool for the diagnosis of psychiatric disorders, which can identify sensitive biomarkers and explore associated signaling pathways.MethodsIn this study, we performed an integrated bioinformatic analysis on 1945… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The remaining 47 papers were published after the seminal paper in 2015 which described seven epileptic patients with SLC6A1 variants ( Carvill et al, 2015 ). Of the 47 clinically relevant papers, two were focused on attention deficit disorder ( Merriman et al, 2015 ; Yuan et al, 2017 , p1), two researched a connection with alcoholism ( Adkins et al, 2015 ; Enoch et al, 2016 ), one found SLC6A1 variants related to Alzheimer’s disease ( Zhu et al, 2020 ), one focused on connections to anxiety ( Sarris et al, 2020 ), three were focused on somatic mutations in malignant tumors ( Eshragh et al, 2017 ; Chen et al, 2020 ; Wang et al, 2022 , p1), one focused on dystonia ( Zech et al, 2017 ), one included multiple gene deletions ( Dikow et al, 2014 ; Yuan et al, 2020 ), four reported SLC6A1 variants associated with schizophrenia ( Frankle et al, 2015 ; Hoftman et al, 2015 ; Zhao et al, 2016 ; Rees et al, 2020 ), three focused on other similar mental health disorders ( Demarest et al, 2019 ; Ahring et al, 2022 ; Knight et al, 2022 ), two described genetic testing technologies ( Schijns et al, 2020 ; Salinas et al, 2021 ), and two described general developmental and epileptic encephalopathies (DEEs) without specific description of patients with SLC6A1 mutation ( Schousboe et al, 2004 ; Guillen-Guio et al, 2018 ; Galer et al, 2020 ; Salinas et al, 2021 ). Only 25 papers included clinical description of patients with neurodevelopmental symptoms and DEEs, with a likely overlap of a few patients between these papers ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 47 papers were published after the seminal paper in 2015 which described seven epileptic patients with SLC6A1 variants ( Carvill et al, 2015 ). Of the 47 clinically relevant papers, two were focused on attention deficit disorder ( Merriman et al, 2015 ; Yuan et al, 2017 , p1), two researched a connection with alcoholism ( Adkins et al, 2015 ; Enoch et al, 2016 ), one found SLC6A1 variants related to Alzheimer’s disease ( Zhu et al, 2020 ), one focused on connections to anxiety ( Sarris et al, 2020 ), three were focused on somatic mutations in malignant tumors ( Eshragh et al, 2017 ; Chen et al, 2020 ; Wang et al, 2022 , p1), one focused on dystonia ( Zech et al, 2017 ), one included multiple gene deletions ( Dikow et al, 2014 ; Yuan et al, 2020 ), four reported SLC6A1 variants associated with schizophrenia ( Frankle et al, 2015 ; Hoftman et al, 2015 ; Zhao et al, 2016 ; Rees et al, 2020 ), three focused on other similar mental health disorders ( Demarest et al, 2019 ; Ahring et al, 2022 ; Knight et al, 2022 ), two described genetic testing technologies ( Schijns et al, 2020 ; Salinas et al, 2021 ), and two described general developmental and epileptic encephalopathies (DEEs) without specific description of patients with SLC6A1 mutation ( Schousboe et al, 2004 ; Guillen-Guio et al, 2018 ; Galer et al, 2020 ; Salinas et al, 2021 ). Only 25 papers included clinical description of patients with neurodevelopmental symptoms and DEEs, with a likely overlap of a few patients between these papers ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…When considering both cases and controls, the top SNP is located near the gene SLC39A12. This gene is highly expressed in brain and was identified by bioinformatic analyses as a significant molecular biomarker in the progression of psychiatric disorders, including bipolar disorder 48 . Moreover, the genes SPTLC1and ROR2 that were associated with YKL-40 level in serum are moderately associated with schizophrenia and bipolar disorder (P = 5.79 × 10 −7 ) according to a previous GWAS 49 .…”
Section: Serum Markersmentioning
confidence: 99%
“…Neuropsychological, neurobehavioral, and the reduced capacity to comprehend new or complex information are widely viewed as hallmarks of mental illnesses. According to the World Health Organization's 2010 report, major depression will be the mental condition that will have the greatest impact on people's lives by 2030, affecting an estimated 450 million people globally [1,2].…”
Section: Introductionmentioning
confidence: 99%